Patterns of sexually transmitted infections: a hospital based cross sectional study - Mohankar, Atul Dilip; Swain, Jyoti Prakash (International Journal Of Community Medicine And Public Health, 2024)
Background: Sexually transmitted infections (STIs) pose a significant public health problem in developing countries like India, which ultimately increases the risk of developing HIV. Understanding the current patterns of STIs in our region of Chhattisgarh state is crucial for implementing strategies to control the spread of infection. The aim of this study was to investigate the patterns of STIs and the associated predisposing factors over the past three years. Methods: A cross-sectional study was conducted from January 2021 to December 2023. A detailed history, clinical examinations, and investigations were performed at CIMS Bilaspur. Diagnoses were made using the syndromic approach, and the data was analyzed for the study. Results: Of the 3495 cases, 2122 (60.71%) were females, and 1373 (39.29%) were males. Vaginal discharge syndrome was the most common STI. There were 48 (1.37%) newly diagnosed HIV cases. Conclusions: The incidence of STIs is higher among the study population, which will increase the risk of HIV transmission henceforth it is important to investigate and manage the sexually transmitted infections.